Evolution of Shale Microstructure under Microwave Irradiation Stimulation - Hu, G.; Sun, C.; Huang, J.; Xu, Guang; Zhu, J. (American Chemical Society, 2018)
As the low permeability of shale gas reservoirs limit its large-scale commercial development, the microwave irradiation stimulation is proposed as a new approach to increase the shale gas reservoir's production. In this study, in order to investigate the microwave's effect on shale pore structure, experiments were performed using nuclear magnetic resonance to compare the pore size distribution of shale samples before and after microwave treatment. The results showed that the numbers as well as sizes of mesopores and macropores in shale samples increased, while the number of micropores decreased after the microwave irradiation. This is benefit to enhance shale gas flow in reservoirs. In addition, the moisture within the shale samples increased its ability to absorb microwave energy, leading to a positive effect on the increase of breathable pores and microfractures. When the accompanying thermal stress and vapor pressure generated inside the shale is larger than the cementation strength between the shale mineral particles, the shale cracks and forms microcracks until it is destroyed. The experimental results demonstrated that the microwave stimulation is effective in expanding breathable pores and inducing fissures in shale samples; it may therefore have applications in enhancing shale gas reservoirs.